Effect of Imagery Training in Technical Training Program on Basketball Free Throw Accuracy Viewed from Intelligence (An Experimental Study to Extracurricular Male Students Of State Senior Secondary School 4 of Pekanbaru) - Gianty, Lisma; Sugiyanto, Sugiyanto; Kristiyanto, Agus (Journal of Education, Health and Sport, 2019)
Imagery training in a technical training program influence the student’s achievement. This type of training has not been applied especially in Male Students of Extracurricular Program in Senior Secondary State School 4 Pekanbaru. The purpose of this study is to find out: 1) The difference in influence between technical training program with imagery training and technical training program without imagery training on the accuracy of basketball free throw 2) The difference in the accuracy of Basketball free throw between students who have high intelligence and the ones who have low intelligence. 3) Effect of interaction between imagery training in technical training program and students’ intelligence on the accuracy of Basketball free throw. This reseach used The 2x2 Factorial Experimental Design Method. The data were collected through Standard Progressive Matrices (SPM) test and the Basketball free throw test. The data were analyzed by using Variance Analysis techniques (ANAVA) with 2 x 2 factorial design at α = 0.05. If the value of F obtained (Fo) is significant, then it is further analyzed by using the Newman-keuls range test. The results of the research as follows : 1) There is an influence between technical training programs with imagery training and technical training programs without imagery training on the accuracy of Basketball free throws. 2) There is a difference in the accuracy of Basketball free throw between students who have high and the ones who have low intelligence. 3) There are interactions between imagery training in technical training program and the students’ intelligence on the accuracy of Basketball free throw.Keywords: Imagery Training, Accuracy, Basketball